Sikh Religious Music in a Migrating Context: The Role of Media - Tiramani, Thea (European Journal of Musicology, 2022)
The aim of this article is to provide an initial study of the relationship between music and media in the Sikh communities in migration. It is easy to notice the great connection between Sikhs all over the world and the homeland: social media, television, Internet, and web radio greatly help Sikhs to create networks and to preserve a strong religious identity. Technologies also allow musical tendencies from India to be gathered and reproduced in the migratory context. Music is a fundamental aspect in the Sikh religion: it is necessary for the religious rites, but also takes on a dominant role in cultural transmission. Based on field research conducted in Sikhs communities in Northern Italy, this article offers practical and concrete examples of how social media and Internet are employed by musicians in the construction and definition of a musical Sikh identity abroad. This can help to develop a more comprehensive view of the music functions in such a complex diaspora community.